Efektivitas Penggunaan Jurnal Langganan Dengan Pendekatan Perceived Usefullness di Perpustakaan Universitas Riau - Deliza Zakir (Perpustakaan Universitas Riau, 2022)
This study aims to determine the causes of user difficulties in using the subscription E-Journal service system and to analyze the access to the subscription e-journal service system at the Riau University library. This research used quantitative methods. The population and sample in this study were students of the University of Riau as many as 100 students, using the Slovin formula. The data collection technique was carried out with a questionnaire containing statements that represented indicators of the perceived usefulness variable. The data was processed using descriptive statistics. The data obtained were tabulated and arranged in tabular form and then the percentage was calculated, and interpreted. The results of this study showed that only 25% of respondents stated that they had accessed the Lib.unri.ac.id website. and 95% access research journals through google search or google schoolar. As many as 97% needed journals for final assignments or other college assignments. 74% stated that the Riau University library did not carry out intensive promotion, and 98% stated that the Riau University library had to carry out intensive promotion. Then it was found that all respondents answered that the library had to do promotions. The conclusion of this study is that the effectiveness of using subscription journals with the Perceived Usefulness function approach for users at the University of Riau cannot be said to be effective and even students tend to barely know it, this is very unfortunate because subscription journals are expensive to use. In this case, In the future, the Riau University library must always carry out continuous and directed promotions.